COVID-19 Vaccination among Czech Dentists - Schmidt, Jan; Perina, Vojtech; Treglerova, Jana; Pilbauerova, Nela; Suchanek, Jakub; Smucler, Roman (Vaccines, 2022)
This work describes and evaluates vaccination against COVID-19 among members of the Czech Dental Chamber during the pre-booster vaccination phase. A cross-sectional online survey was conducted between 23 June and 4 September 2021, among 2716 participants, representing 24.3% of all chamber members. A total of 89.5% of respondents stated that they were registered for vaccination against COVID-19, their vaccination had started or been completed, or had a medically relevant reason to avoid vaccination. A total of 79.6% of respondents stated that they were fully vaccinated, most of them with the Comirnaty (Pfizer-BioNTech) vaccine (88.3%). The vaccination rate among males was significantly higher than among females (p = 0.001, OR 1.48). The main reasons for vaccination were professional (91.5%). The share of fully vaccinated participants was significantly higher (p < 0.0001, OR = 8.17) compared to the Czech general population (30.8%). A COVID-19 vaccine breakthrough infection rate was 0.42%. The study shows that both the willingness to vaccinate and the proportion of fully vaccinated individuals among Czech dentists are high, and only about 10% of them refused vaccination based on reasons classified as not medically relevant.